Model Rantai Markov Pangsa Pasar Operator Selular di Universitas Bina Nusantara, Jakarta Barat - Tjoe, Tjia Fie; Sarjono, Haryadi (Journal the Winners: Economics, Business, Management, and Information System Journal, 2007)
Article presented the replacement of cellular cards operator service user, especially for GSM of five operators that are dominant in Indonesia, those are Â XL, Mentari, Simpati, AS, and IM3 for six months with teenagers sample of 295 students from Management Department of Bina Nusantara University. The used method was Markov analysis. Besides that, it also used State and Probability State that were used to identify the whole possible situation of a process or system. Based on the research, from 295 samples of teenagers, it can be seen that there is a switching from one provider into another.